Evaluation of Paramedic Utilization of the Intubating Laryngeal Mask Airway in High-Fidelity Simulated Critical Care Scenarios. Issue 6 (4th September 2013) - Byars, Donald; Lo, Bruce; Yates, Jeff
Abstract Introduction Successful oxygenation and ventilation can mean the difference between life and death in the prehospital setting. While airway challenges can be numerous within the confines of the emergency department, there are many additional confounding difficulties in the prehospital setting, which include limited access to equipment, poor lighting, extreme environments, limited personnel to assist, no immediate backup, and limited rescue airway options. The concept of an easy, reliable, and rapidly deployable alternative rescue airway device is critical, especially when considering the addition of rapid sequence intubation protocols in the prehospital setting. Hypothesis The primary objective of this study was to ascertain whether paramedics can be trained to deploy this alternative airway device with an acceptable success rate in a simulated critical care airway scenario. The secondary objective was to determine whether the previously-trained paramedics were able to retain their ability to deploy the device successfully at one year. Methods This was a prospective, observational, single-group, descriptive cohort, educational trial. Forty paramedics were trained in the use of the Intubating Laryngeal Mask Airway (I-LMA) in a simulation medicine curriculum culminating in a simulated critical care difficult airway scenario requiring urgent oxygenation and ventilation after failed traditional endotracheal intubation. An emergency medicine physician proctor determined successful airway management. Repeat testing was then performed at approximately one year out, challenging the medics to intubate a mannequin using the I-LMA during an unrelated training session. Results Of the 40 paramedics who underwent complete simulation training, 39 were able to intubate and ventilate the simulated difficult airway using the I-LMA during the critical care scenario. This yields a success rate of 97.5% (95% CI, 87.1%-99.4%). At approximately one year out, 35 out of 35 medics were able to intubate the mannequin using the I-LMA, resulting in a success rate of 100% (95% CI, 91.4%-100%). Conclusions In this study, paramedics were able to deploy the I-LMA with a high degree of success in a simulated difficult airway, with a high degree of skill retention at one year out. <mixed-citation publication-type="journal"> <string-name> <given-names>D</given-names> <x content-type="archive" xml:space="preserve"> </x> <surname>Byars</surname> </string-name>, <string-name><given-names>B</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Lo</surname></string-name>, <string-name><given-names>J</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Yates</surname></string-name>. Evaluation of paramedic utilization of the Intubating Laryngeal Mask Airway in high-fidelity simulated critical care scenarios . <source>Prehosp Disaster Med.</source><year>2013</year>;<volume>28</volume>(<issue>6</issue>):<fpage>1</fpage>-<lpage>2</lpage></mixed-citation>.